2020
DOI: 10.1212/wnl.0000000000009316
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities mediate the association of nocturnal blood pressure with cognition

Abstract: ObjectiveTo test the hypotheses that hypertension and nocturnal blood pressure are related to white matter hyperintensity (WMH) volume, an MRI marker of small vessel cerebrovascular disease, and that WMH burden statistically mediates the association of hypertension and dipping status with memory functioning, we examined the relationship of hypertension and dipping status on WMH volume and neuropsychological test scores in middle-aged and older adults.MethodsParticipants from the community-based Maracaibo Aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 51 publications
3
24
0
Order By: Relevance
“…Some researchers have suggested that APOE-4 predisposes carriers to cerebrovasculature damage by hypertension [39]. Both APOE-4 and altered nocturnal dipping profile have been associated with increased white matter hyperintensity volume [40,41]. Therefore, the results presented here support the notion that co-occurrence of APOE-4 and increased nighttime BP may increase the likelihood of small vessel disease, which in turn increases the likelihood of DAT development.…”
Section: Discussionsupporting
confidence: 80%
“…Some researchers have suggested that APOE-4 predisposes carriers to cerebrovasculature damage by hypertension [39]. Both APOE-4 and altered nocturnal dipping profile have been associated with increased white matter hyperintensity volume [40,41]. Therefore, the results presented here support the notion that co-occurrence of APOE-4 and increased nighttime BP may increase the likelihood of small vessel disease, which in turn increases the likelihood of DAT development.…”
Section: Discussionsupporting
confidence: 80%
“…To further examine the relationships among cerebrovascular morphologies, high BP, and WMH, the mediation analysis was conducted with a linear single-mediator model. 22,23 The mediation models used cerebrovascular morphologies as the mediator, WMH status as the response, and treated BP as the determinant. Confounders including age, sex, body mass index, and whole brain volumes were adjusted for each mediation model.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Besides daytime BP profile, nighttime BP is also emerging as a relevant contributor to cardiovascular health and disease. Consistent with this, poor nocturnal BP control, expressed as reverse dipping, appears to have a relevant role in hypertension-associated small vessel cerebrovascular disease and related memory impairment [ 19 ]. A particularly detrimental effect of reverse dipping on cognitive function has been described in elderly adults [ 19 , 20 ].…”
Section: Hypertension Control and Neuroprotectionmentioning
confidence: 80%